(untitled) (Research, Society and Development, 2021)
This is an exploratory, cross-sectional study carried out with 314 non-institutionalized elderly people linked to a chronic disease management program sponsored by a health plan operator located in the city of São Paulo, where these people live, during between the second semester of 2018 and the first of 2019. The objective, after comparing groups of elderly people with and without sensory losses - visual, auditory and double loss -, is to verify their interaction with variables related to functional capacity and detect which factors influence the presence of double loss. Data was collected related to which and how many chronic diseases were present, the number of medications of continuous use normally taken, the presence of visual and / or hearing loss diagnosed and constant monitoring by a doctor or speech therapist. Were applied scales to assess the functional capacity of these people. After descriptive analysis, the group was segmented in order to achieve the research objectives, using the Chi-Square, Fisher’s Exact and t-Student tests. Afterwards, logistic regression was performed, which made it possible to examine the variables with the greatest influence in relation to isolated sensory losses and DPS (Odds ratio). Sensory losses proved to be significant in compromising functional capacity, affecting performance for basic activities and restricting mobility. Widowhood associated with the double loss was an unprecedented finding. For this group, advanced age was an important predictive factor for the appearance of sensory losses, especially Double Sensory Loss and having a previous hearing or visual loss increases the risk for their development.